Age estimation in the living: A scoping review of population data for skeletal and dental methods. (March 2021) - Cummaudo, Marco; De Angelis, Danilo; Magli, Francesca; Minà, Giulia; Merelli, Vera; Cattaneo, Cristina
Highlights: Methods for age estimation in the living should be tested on different populations. A scoping review on population data for age estimation methods was conducted. Two hundred studies on the rate of skeletal maturation were found. Four hundred thirty-nine studies on the rate of dental maturation were found. For most of western and central African countries there are currently no population data. Abstract: Age estimation of living individuals has become a crucial part of the forensic practice, especially due to the global increase in cross-border migration. The low rate of birth registration in many countries, hence of identification documents of migrants, especially in Africa and Asia, highlights the importance of reliable methods for age estimation of living individuals. Despite the fact that a number of skeletal and dental methods for age estimation have been developed, their main limitation is that they are based on specific reference samples and there is still no consensus among researchers on whether these methods can be applied to all populations. Though this issue remains still unsolved, population information at a glance could be useful for forensic practitioners dealing with such issues. This study aims at presenting a scoping review and mapping of the current situation concerning population data for skeletal (hand-wrist and clavicle) and dental methods (teeth eruption and third molar formation) for age estimation in the living. Two hundred studies on the rate of skeletal maturation and four hundred thirty-nine on the rate of dental maturation were found, covering the period from 1952 and 2020 for a total of ninety-eight countries. For most of the western and central African countries there are currently no data on the rate of skeletal and dental maturation. The same applies to the countries of the Middle East, as well as the eastern European countries, especially as regard the skeletal development.